Alkaline KMnO4 solution pretreat hydrochar to prepare high ultra-micropore volume carbon for CH4 enrichment from low-concentration coalbed methane. (1st November 2021) - Liu, Fuxin; Lin, Qian; Fu, Chengbin; Wang, Meng; Han, Meng; Huang, Chen; Pan, Hongyan; Liu, Fei
Graphical abstract: Highlights: Carbon adsorbents are prepared by a novel method of alkaline KMnO4 solution pretreating carbon precursor combine with NH3 removing intercalated alkali metal. Prepared carbon adsorbents have a high ultra-micropore volume. The sample AC-KP exhibited high CH4 adsorption capacity of 1.88 mmol/g and high CH4 /N2 selectivity of 6.5 at 298 K and 101.3 kPa. The sample AC-KP is significantly superior to many MOFs and other carbon materials and has good cycling performance. Abstract: Rational design of the carbon adsorbent for recycling CH4 from low-concentration coalbed methane is impressive for sustainable development. However, facile approaches to prepare carbon materials with uniform pore size distribution and abundant ultra-micropore volume are still challenging. Herein, we designed a facile and effective strategy to produce ultra-microporous carbon material, which uses alkaline KMnO4 solution to pretreat carbon precursor, then activate at high temperature. The prepared carbon material has a microspherical morphology, uniform pore size distribution of mainly 0.4–0.7 nm and abundant ultra-micropore volume of 0.50 cm 3 /g. The excellent CH4 adsorption capacity was demonstrated by the adsorption data with 3.38 mmol/g, 1.87 mmol/g at 273 K, 298 K and 101.3 kPa. The IAST simulation suggested the CH4 /N2 selectivity of sample AC-KP for a binary mixture of CH4 and N2 was 6.5 at 298 K and 101.3 kPa. Meanwhile, the adsorption capacity of the binary mixture of CH4 and N2 was also calculated. The fixed bed cycling breakthrough experiment showed good recycling performance with the regeneration rate maintained at about 95% in eight cycles. This work provides a promising avenue to carbon materials with abundant ultra-microporosity towards the superior performance of CH4 recycling from low-concentration coalbed methane.